Artificial Intelligence vs. Traditional Research Methods: An Empirical Study from Northern Croatia - Katerina Fotova Čiković; Antonija Mandić; Maja Hoić (Tehnički Glasnik)
Due to the emergence and increased development of Artificial Intelligence (AI), research in general has been significantly impacted, particularly in the field of scientific theories and models. The purpose of this study is to analyze the acceptance of both AI tools and traditional methodologies used in research. Moreover, conclusions about the respondents' perception and openness to using AI tools in research regarding gender, age and current academic position are discussed. Another goal is to compare the level of satisfaction from both the AI tools and the traditional research methods. A questionnaire-based survey was carried out between February and March 2024, and it included students and teaching staff at the University North in Croatia. The novelty of this research is mirrored in the scarcity of such empirical studies encompassing the academic community in Croatia.